Linking widowhood and later-life depressive symptoms: Do childhood socioeconomic circumstances matter?. (28th October 2022) - Recksiedler, Claudia; Cheval, Boris; Sieber, Stefan; Orsholits, Dan; Stawski, Robert S.; Cullati, Stéphane
Abstract: Objectives: Widowhood and adverse childhood socioeconomic circumstances (CSC) have both been linked to increased levels of depressive symptoms in old age. Beyond their independent impact on depressive symptoms, experiencing adverse CSC may also trigger a cascade of cumulative adversity and secondary stressors across the life course that shapes how individuals weather stressful life events later on. Method: We examine whether exposure to adverse CSC moderates the relationship between later-life widowhood and depressive symptoms using data from the Survey of Health, Ageing and Retirement in Europe (2004-2017). Results: Mixed-effects models revealed that both widowhood and adverse CSC were associated with increased levels of depressive symptoms among men and women. Associations between widowhood and depressive symptoms, however, were not moderated by CSC for both genders. Conclusion: Persisting differences in the levels of mental health in response to later-life widowhood did not further widen in the presence of disparities experienced early in the life course. This may reflect the life-altering impact of this age-normative, yet stressful life event across the social strata.